Introduction - Brown, Duncan; Krog, Antjie (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
In the piece ‘Creative Non-Fiction: A Conversation’, we argued that ‘creative non-fiction has become in a sense “the genre” of South African writing, [...] writing which makes its meanings at the unstable fault line of the literary and journalistic, the maginative and the reportorial’ (2011: 57): recently, the work of Sihle Khumalo, Jacob Dlamini, Max du Preez, Rian Malan, Kevin Bloom, Denis Beckett, Shaun Johnson, Antjie Krog, Jonny Steinberg, Stephen Otter, John Carlin, Njabulo S. Ndebele, Jeff Opland, Julia Martin, Sarah Nuttall, Liz McGregor, Hedley Twidle, Duncan Brown; historically, Sol T. Plaatje, Can Themba, Nat Nakasa, Todd Matshikiza, Alan Paton, H. I. E Dhlomo, and many more. Perhaps more broadly, and recognising the important work of ‘Northern’ writers in this genre, we would argue that creative non-fiction has become a particularly significant genre of the global ‘South’, in which its imaginative engagement with ‘truth telling’ has been profoundly enabling in narrating pasts and presents characterised by injustice, inequality, division, and the need to ‘uncover’. It has also enabled writers to bring their own singular life and surroundings into an imagined narrative.